Diagnostic spectrum of multifocal motor neuropathy. Issue 2 (5th June 2013) - Matsui, Naoko; Miyashiro, Ai; Shimatani, Yoshimitsu; Nodera, Hiroyuki; Izumi, Yuishin; Kuwabara, Satoshi; Baba, Masayuki; Komori, Tetsuo; Sonoo, Masahiro; Mezaki, Takahiro; Kawamata, Jun; Hitomi, Takefumi; et al.
Abstract Objective We carried out a retrospective study to define clinical features in a large series of patients with multifocal motor neuropathy (MMN) and to assess the diagnostic spectrum of MMN. Methods The study consisted of 46 patients with MMN between 2005 and 2009 from 19 major neuromuscular centers in Japan. The 2006 European Federation of Neurological Societies (EFNS)/Peripheral Nerve Society (PNS) criteria (hereafter, original criteria) and the efficacy of intravenous immunoglobulin (IVIg) therapy were taken into consideration in the diagnosis of MMN. The main parameters were clinical features and electrophysiological findings. The Japanese MMN Study Group designed a set of recommended criteria to reduce the frequency of underdiagnosis. Furthermore, we verified the diagnostic spectrum of MMN using both the original criteria and the recommended criteria. Results Clinical features were similar to those of previous studies. A total of 25 of the 46 patients (54.3%) showed conduction block (CB); that is, nearly half of the patients did not satisfy the original criteria. The Japanese MMN Study Group included findings indicative of focal demyelination, namely, activity‐dependent CB and asymmetric abnormality of F‐waves in the electrophysiological test, in the recommended criteria. By doing so, the diagnostic sensitivity of the recommended criteria was increased by 17.4% compared with that of the original criteria. Conclusions The recommended criteria designed by the Japanese MMN Study Group showed higher diagnostic sensitivity than the original criteria, but no significant difference was found between them. A prospective study using the recommended criteria might reduce the frequency of underdiagnosis in patients with MMN.